Overall outcome, functioning, and disability in older adults 3 to 14 years after traumatic brain injury - von Seth, Charlotta; Lewén, Anders; Lannsjö, Marianne; Enblad, Per; Lexell, Jan (PM and R, 2025)
Background: Epidemiological studies show an increasing incidence of traumatic brain injury (TBI) among people aged 65 years and older. Advances in neurointensive care have improved survival after TBI. There is a need for knowledge about long-term outcome after TBI among older survivors of TBI. Objective: To describe the overall outcome, long-term functioning, and disability of the participants in the Uppsala Long-term outcome in Older adults with Traumatic brain injury Study (U-LOTS), a cohort study assessing adults aged 60 years or older when admitted to a neurointensive care unit following a TBI, where 3 to 14 years had passed since the injury. Design: Cross-sectional cohort study. Setting: Home and community settings. Interventions: Not applicable. Participants: Data were collected from 79 survivors of TBI (65% men; mean age 76 years, mean time since TBI 7 years). Main Outcome Measures: The Glasgow Outcome Scale Extended (GOSE), the Functional Independence Measure (FIM), the Mayo-Portland Adaptability-4 (MPAI-4), and the following sociodemographics and TBI characteristics: gender, age, marital status, vocational situation, rehabilitation, need of assistance, use of mobility devices, oropharyngeal dysphagia, impaired sense of smell and/or taste, prior brain disease, cause of accident, severity of TBI, comorbidities, dominant finding on first computed tomography scan, and assessment with GOSE 6 months after TBI. Results: Falls (68%) and acute subdural hematoma (41%) were the most common cause and injury. For many participants (40%) the GOSE scores did not change between 6 months after TBI until the long-term follow-up, and a majority (57%) had a relatively good outcome as assessed with the MPAI-4. GOSE, FIM, and MPAI-4 Ability scores were significantly (p <.05) correlated with injury severity. Marital status remained unchanged for 70% of the participants. Conclusions: Older adults surviving a TBI may have a relatively favorable outcome. A major factor that determined long-term outcome was injury severity.
Publisher Copyright: © 2025 The Author(s). PM&R published by Wiley Periodicals LLC on behalf of American Academy of Physical Medicine and Rehabilitation.